Guidelines for Nonlinear Finite Element Analysis of Reinforced Concrete Columns with Various Types of Degradation Subjected to Seismic Loading - Seyed Sasan Khedmatgozar Dolati; Adolfo Matamoros; Wassim Ghannoum (Infrastructures)
Concrete columns are considered critical elements with respect to the stability of buildings during earthquakes. To improve the accuracy of column damage and collapse risk estimates using numerical simulations, it is important to develop a methodology to quantify the effect of displacement history on column force–deformation modeling parameters. Addressing this knowledge gap systematically and comprehensively through experimentation is difficult due to the prohibitive cost. The primary objective of this study was to develop guidelines to simulate the lateral cyclic behavior and axial collapse of concrete columns with different modes of failure using continuum finite element (FE) models, such that wider parametric studies can be conducted numerically to improve the accuracy of assessment methodologies for critical columns. This study expands on existing FEM research by addressing the complex behavior of columns that experience multiple failure modes, including axial collapse following flexure–shear, shear, and flexure degradation, a topic which has been underexplored in previous works. Nonlinear FE models were constructed and calibrated to experimental tests for 21 columns that sustained flexure, flexure–shear, and shear failures, followed by axial failure, when subjected to cyclic and monotonic lateral displacement protocols. The selected columns represented a range of axial loads, shear stresses, transverse reinforcement ratios, longitudinal reinforcement ratios, and shear span-to-depth ratios. Recommendations on optimal material model parameters obtained from a parametric study are presented. Metrics used for optimization include crack widths, damage in concrete and reinforcement, drift at initiation of axial and lateral strength degradation, and peak lateral strength. The capacities of shear–critical columns calculated with the optimized numerical models are compared with experimental results and standard equations from ASCE 41-17 and ACI 318-19. The optimized finite element models were found to reliably predict peak strength and deformation at the onset of both lateral and axial strength failure, independent of the mode of lateral strength degradation. Also, current standard shear capacity provisions were found to be conservative in most cases, while the FE models estimated shear strength with greater accuracy.